BEHAVIORAL IMPACT OF IMITATING ONLINE GAME SAKURA SCHOOL SIMULATOR - Jannah, Miftakul; Wardana, Mahardika Darmawan Kusuma (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
Abstract :This research was conducted against the background of the impact on students playing the online game sakura school simulator on changes in social behavior imitating elementary school students. The purpose of this study was to determine the impact of students playing the online game sakura school simulator on the social behavior of imitating students at Madarasah Ibtidaiyah. This study uses qualitative methods with case study instruments, collecting data from online game players through direct observation, interviews and documentation. Based on the results of the study, it was concluded that playing the online game sakura school simulator had an impact on imitating social behavior in students. Children are very easy to imitate or imitate a model that is found and desired to be imitated. The results of imitating the online game sakura school simulator can be shown directly or in the future. The procedures carried out in the imitation process include (1) the process of paying attention, (2) the process of remembering, (3) motor reproduction, and (4) the reinforcement and motivational process.Keywords: online games, imitating social behavior